ANÁLISIS DE LA PROBLEMÁTICA DEL FEMINICIDIO EN UN POSIBLE ESCENARIO DE POSCONFLCITO (2016)
This paper highlights the interdependence between public and private contexts of relationship, which is evident in the normalization of violence as a means of resolving conflicts. This normalization is the result of a history characterized by armed confrontations, especially since the establishment of guerrilla and paramilitary organizations in the country. In parallel to this normalization, it found the consolidation of gender imaginary that relegate women to a position of victim or sexual object, this is reflected in the actions of the fighters, both in actions taken in the context of the confrontation, as is those developed after the surrender of weapons. Against this background, this paper presents the need to consider such imaginary gender, especially those individuals whose notions of thought were shaped by their membership in a military organization, taking into account the possible post-conflict scenario and therefore the output of the war hundreds of men and women combatants; this to prevente violence against women, specifically acts of femicide. In this sense, the formulation of strategies for the prevention and eradication of violence against women should consider not only punitive measures, as the recent Act 1671, but also the reconstruction of the structures of thought that support such violence.